Factors Influencing Mexican Women's Decisions to Vaccinate Daughters Against HPV in the United States and Mexico. Issue 4 (October 2016) - Wentzell, Emily; Flores, Yvonne N.; Salmerón, Jorge; Bastani, Roshan
Abstract : Mexican and Mexican-American women bear high cervical cancer burdens, yet relationships between mothers' experiences of vaccinating daughters against cervical cancer-causing human papillomavirus (HPV) on both sides of the border are unknown. We surveyed 400 Mexican-born women in Oxnard, California, United States and Cuernavaca, Morelos, Mexico, about their beliefs and practices regarding daughters' HPV vaccination, conducting in-depth interviews with 35 participants. Contextualizing interview findings in survey data, we identify key factors influencing mothers' experiences regarding daughters' HPV vaccination in both countries. Although US acculturation influenced some participants' concerns, US and Mexico participants overwhelmingly desired eventual vaccination; structural rather than cultural barriers limited vaccine uptake.